Modern technologies in the development of higher education teachers’ professional competence - T. V. Manchenko; I. N. Guchetl (Вестник Майкопского государственного технологического университета)
The relevance of the research. The current stage of the historical development of the world community is characterized by the acceleration of scientific, technical and social progress, the large-scale dissemination of new ideas and technologies. Therefore, the reproduction of knowledge carriedout on an innovative basis is relevant and has an increasing impact on the rate of economic growth.   The problem statement. The modern education system is gradually beginning to fully use theresources of the competency-based approach. In vocational education this approach is the conceptual basis for the implementation of an innovation system. The problem of the research is to identify the features of the formation of professional competence of higher education teachers.   The purpose of the article is to substantiate modern technologies for developing the professional competence of vocational education teachers to increase their readiness to train future specialists on innovative principles.   The research methods used are theoretical analysis of scientific literature on the research problem; study of regulatory documents in the field of education; analysis and synthesis; systematization and generalization; survey.   The results and key conclusions. The need for continuous professional development of teachers based on innovative principles and updating of the problem under consideration has been identified. The use of modern pedagogical technologies of distance learning, project-based learning and production technologies for the formation of professional competence of higher education teachers, as well as modern forms of training future qualified specialists, have been justified.